2019
DOI: 10.1021/acsabm.9b00970
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Endothelial Cell Adhesion and Antithrombogenicity of Polytetrafluoroethylene by Chemical Grafting of Chondroitin Sulfate

Abstract: Polytetrafluoroethylene (PTFE) is one of the polymers extensively applied in biomedicine. However, the application of PTFE as a small-diameter vascular graft results in thrombosis and intimal hyperplasia because of the immune response. Therefore, improving the biocompatibility and anticoagulant properties of PTFE is a key to solving this problem. In this study, a hydroxyl group-rich surface was obtained by oxidizing a benzoin-reduced PTFE membrane. Then, chondroitin sulfate (CS), an anticoagulant, was grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…[ 25 ] When chondroitin sulfate was grafted on the surface of the SPEEK sample, a new peak at 1729 cm –1 should be attributed to the C═O stretching vibrations of −COOH groups, and the −COO − symmetric vibrations and N−H bonds of CS at 1374 cm –1 and 3394 cm –1 were observed in the spectra of SPEEK‐CS. [ 22,25 ] This result suggested that CS was successfully grafted to the surface of the SPEEK sample. We observed that the absorption peak 1729 cm −1 became weaker in the spectra of SPEEK‐CS@Sr, which could be assigned to the deprotonation of −COOH groups that was caused by the coordination of CS and Sr ions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 25 ] When chondroitin sulfate was grafted on the surface of the SPEEK sample, a new peak at 1729 cm –1 should be attributed to the C═O stretching vibrations of −COOH groups, and the −COO − symmetric vibrations and N−H bonds of CS at 1374 cm –1 and 3394 cm –1 were observed in the spectra of SPEEK‐CS. [ 22,25 ] This result suggested that CS was successfully grafted to the surface of the SPEEK sample. We observed that the absorption peak 1729 cm −1 became weaker in the spectra of SPEEK‐CS@Sr, which could be assigned to the deprotonation of −COOH groups that was caused by the coordination of CS and Sr ions.…”
Section: Resultsmentioning
confidence: 96%
“…[21] Subsequently, chondroitin sulfate was grafted on the surface of the SPEEK sample based on the Schiff base reaction between PEEK and ethylenediamine (EDA) and the amidation reaction between PEEK and CS. [19,22] Later, we utilized the chelation effect between Sr ions and chondroitin sulfate (CS) to introduce Sr into the surface of SPEEK-CS sample for forming the SPEEK-CS@Sr sample. This is an economic, simple, and feasible method to achieve the surface modification of PEEK with polysaccharides, as the carboxy functional group widely existed in various polysaccharides' structures.…”
Section: The Surface Physicochemical Characterization Of the Samplesmentioning
confidence: 99%
“…However, Gt/PCL composite nanofibers still have some limitations, such as slow endothelialization, and thrombosis. Recently, chondroitin sulfate (CS) is a sulfated polysaccharide containing glycosaminoglycan and galactosamine, which has been demonstrated to possess high adhesion to endothelial cells (ECs), weak interaction to proteins and platelets, as well as electrostatic repulsion of negatively charged blood components [15][16][17]. In addition, CS could inhibit cellular apoptosis and facilitate the healing of vascular wounds [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [17] reported a method for PTFE functionalization with hydroxyl groups using pre-treatment with benzoin. The PTFE membranes were then treated with chondroitin sulfate and an anticoagulant was grafted on the surface of the hydroxylated PTFE membrane using 3-aminopropyltriethoxysilane.…”
Section: Introductionmentioning
confidence: 99%